NaIO4-mediated C-H activation of alkylbenzenes and alkanes with LiBr - Shaikh, T. M.; Sudalai, A. (Tetrahedron Letters, 2005)
NaIO4 oxidizes lithium bromide efficiently under acidic conditions to functionalize alkylbenzenes and alkanes and produce the corresponding bromo and acetoxy derivatives in excellent yields. The protocol also demonstrates the direct conversion of cyclohexane into trans-1,2-dibromocyclohexane in moderate yield. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: alkanes; alkylbenzenes; C-H activation; Lithium bromide; NaIO4

Titanium superoxide catalyzed selective oxidation of phenols to p-quinones with aq. H2O2 - Dewkar, Gajanan; Shaikh, T. M.; Pardhy, S.; Kulkarni, S. S.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
Titanium superoxide, a novel heterogeneous and readily accessible catalyst, is found to catalyze the selective oxidation of phenols to the corresponding 1,4-benzoquinones in preparative yields with aq. 30% H2O2 as oxidant under mild reaction conditions.